(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: Periodic estimate of periodontal disease burden is crucial for developing novel treatment options, evaluating prevention strategies, and devising new policies. The last national survey of adolescents was conducted 15 years ago. As part of an oral health assessment survey done. Aim’s & Objectives: this study aimed to determine the prevalence of periodontal disease among older teenage pupils and investigate its determinants. Materials and Methods: Examining 1,065 individuals between the ages of 15 and 18 from government and private schools in chosen urban and rural areas of five districts of Kerala using a multistage cluster sampling technique. Sociodemographic and oral health behaviour information, the modified Community Periodontal Index, the Oral Hygiene Index Simplified, and the Dental Aesthetic Index were collected. To determine the predictors of gingival bleeding and periodontal pockets, descriptive statistics, bivariate and multivariate logistic regression analyses were conducted. Results: The prevalence of gingival bleeding, periodontal pockets, and loss of attachment were, respectively, 42%, 13.4%, and 2.7%. In the adjusted multivariate model for predictors of gingival bleeding, residing in a rural area, attending government schools, having a mother with a high level of education and their employment status, need for orthodontic treatment, oral hygiene frequency, and poor oral hygiene status emerged as significant predictors. In the multivariate model for periodontal pockets, bleeding upon probing emerged as the greatest predictor, with an odds ratio of 12.85 when oral hygiene was accounted for. Conclusion: Prevalence of periodontal disease in adolescents is substantial. Significant predictors of periodontal disease in teenagers include sociodemographic variables, poor dental hygiene, and malocclusion.